MEMAHAMI DIALEKSI KONFLIK KERJA DAN PENGALAMAN KOMUNIKASI KARYAWAN DALAM PROSES RESOLUSI KONFLIK DI KANTOR IMIGRASI PADANG - Novena Puji Astuti; Ernita Arif; Elva Rona Ningroem (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This research was motivated by the emergence of work conflict in the scope of work in Padang Immigration Office. It happens because employees have different cultural characteristics and characters. The purpose of this study was to understand how the dialectics of conflict occur in employees and understand how the communication experience of employee in the process of resolving work conflicts. The study was conducted using Leslie A. Baxter's Relational Dialectic Theory, conducted on 10 employees using the phenomenological analysis method of Van Kaam. The results showed that the dialectic of conflict between employees occurred quite varied. First, there is a contradiction between the desire to get closer or distance themselves if there is a conflict. Second, competition contradiction of positions occured, because between employees have the nature of competing to achieve life goals. Third, contradictions between the desire to be open or closed with fellow employees, the informants try to open each other but still have confidential information in colleague's relationships. Communication experience in the conflict resolution process, used by employees is effective or ineffective conflict management.